2021
DOI: 10.31113/jia.v18i2.754
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Culture and Employee Performance: Assessing the Influence on the Implementation of Public Services During The Covid 19 Pandemic

Abstract: Public service providers during the COVID-19 pandemic face challenges in realizing quality services. At this time, service providers need the support of an organizational culture that is sensitive to change and optimal employee performance. Therefore, to determine the influence of organizational culture and employee performance in public services, this study is directed to analyze organizational culture and employee performance in supporting the implementation of quality public services in agencies engaged in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…Beberapa penelitian terkait pengaruh antarvariabel budaya organisasi dan program retensi terhadap kinerja tenaga pendidik melalui engagement tenaga pendidik telah dilakukan oleh Brenyah dan Obuobisa-Darko (2017); Hilmi et al (2013); Motlou et al (2016); Adhitama dan Riyanto (2020); Bahagia dan Putri (2020); Chanana (2020); Elsafty dan Ragheb (2020); Widyawati et al (2021). Penelitian ini memiliki kesamaan untuk mengukur variabel penelitian saat situasi wabah COVID-19.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Beberapa penelitian terkait pengaruh antarvariabel budaya organisasi dan program retensi terhadap kinerja tenaga pendidik melalui engagement tenaga pendidik telah dilakukan oleh Brenyah dan Obuobisa-Darko (2017); Hilmi et al (2013); Motlou et al (2016); Adhitama dan Riyanto (2020); Bahagia dan Putri (2020); Chanana (2020); Elsafty dan Ragheb (2020); Widyawati et al (2021). Penelitian ini memiliki kesamaan untuk mengukur variabel penelitian saat situasi wabah COVID-19.…”
Section: Pendahuluanunclassified
“…Persepsi responden menyatakan bahwa pelaksanaan budaya organisasi di SIT telah dilakukan namun namun belum berpengaruh signifikan terhadap kinerja. Hasil temuan ini sesuai dengan kajian yang dilakukan oleh Widyawati et al (2021), yaitu budaya organisasi yang negatif adalah penyebab dari tidak maksimalnya kinerja tenaga pendidik. Pada penelitian lain dinyatakan bahwa budaya organisasi yang diterapkan dengan baik mampu mempengaruhi kinerja tenaga pendidik (Muttaqin et al, 2020).…”
Section: Analisis Inner Modelunclassified
“…A study conducted in Newspaper Company in Malaysia showed that an organizational culture that values work achievement encourages employee performance (Sundararajan et al, 2020). In the healthcare industry, organizational culture has a role in performance through the mediation of good leadership and financial management (Widyawati et al, 2021). In the analysis of port employee performance in Tarakan Kalimantan, it was shown that organizational culture has a direct influence on performance.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Public services in Indonesia are the most frequently discussed topic (Djamrut, 2015;Meyliano & Putra, 2018;Widyawati et al, 2021). This is because the services provided so far have not been able to meet community satisfaction.…”
Section: A Introductionmentioning
confidence: 99%